“KEEP YOUR EYES ON THE PRIZE”: CONGRESSMAN JOHN LEWIS’S PROVERBIAL ODYSSEY FOR CIVIL RIGHTS - Mieder, Wolfgang (Proverbium - Yearbook, 2014)
While this is a scholarly study of the proverbial language in John Lewis’s (born 1940) three books Walking with the Wind: A Memoir of the Movement (1998), Across that Bridge: Life Lessons and a Vision for Change (2012), and March: Book One (2013), it is also a somewhat personal laudation of this U.S. Congressman from the state of Georgia, who is the last surviving member of the six major leaders of the Ameri-can civil rights movement of the 1950s, 1960s, and 1970s. He was the chairman of SNCC (Student Nonviolent Coordinating Committee) that played a significant role in getting students and others from the North and the South of the United States actively involved in the slow process of desegregation and the advancement of civil and human rights for African Americans and the population at large. His impressive sociopolitical rhetoric is informed by the traditional sermonic style of Baptist preachers and by the rhetorical prowess of his idol and friend Martin Luther King. Lewis’s language is replete with proverbs from the Bible, quotational proverbs from the American democratic tradition, and folk proverbs as well as proverbial expressions. Numerous examples are cited in context accompanied by interpretive comments, showing that this proverbial language is part and parcel of his highly informative and emotive style. In fact, his autobiography Walking with the Wind with its proverbial title is not only a classic personal account of the experienced civil rights movement but also an extremely well written document due in large part to its numerous proverbial metaphors. Following a bibliography is a complete index of the 742 proverbial text included in the three books.